The use of horizontal and inclined bars as shear reinforcement - Abdul Hamid, Noor Azlina (2005)
Shear failure in beams are caused by diagonal cracks near the support. Any form of effectively anchored reinforcement that intersects these cracks will be able to resist the shear stress to a certain extent. This project presents the results of an experimental investigation on six reinforced concrete beams in which their structural behaviour in shear were studied. All the beams were cast with the same grade of concrete, and provided with identical amount of main reinforcement. In order to investigate the contribution of the additional horizontal and independent bent-up bars to the shear carrying capacity of the beam, two specimens each were provided with horizontal longitudinal bars and bent-up bars in the high shear region. Two different quantities of additional bars in each of these cases were adopted. The fifth specimen was provided with sufficient amount of shear reinforcement in terms of vertical links, while the other one was cast without any shear reinforcement to serve as control specimens. The performances of the beams in resisting shear in the form of deflection, cracking, strain in the shear reinforcement and ultimate load were investigated. The results show that the shear capacities of the beams with additional horizontal and independent bent-up bars larger than 1.2% of their cross-sectional area are higher than that of the conventionally designed beam with vertical links. It may therefore be suggested that these types of shear reinforcement be used to ease the congestion of links near the supports